Inovasi Pembelajaran di Sekolah Dasar: Pemanfaatan Teknologi dan Model Pembelajaran untuk Meningkatkan Hasil Belajar dan Minat Siswa - Yarisda Ningsih; Nur Azmi Alwi; Nur Azizah; Rafa Fauziyyah; Chalisa Feyruz Firdaus (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This article discusses the use of technology and learning models on student learning outcomes and interests in elementary schools. In elementary schools, learning innovation is very important to improve education and student learning outcomes. Using technology and implementing innovative learning models as a strategy to make learning more effective, interesting, and meaningful. Interactive applications, digital devices, and online platforms are some of the technologies that help students be more actively involved in class, such as quizz application training, digital dictionaries, educational games, learning videos, and so on that make learning more fun and interactive. In addition, learning models such as project-based learning (also known as Project-Based Learning), cooperative learning Think Pair Share, and problem-based learning are used to improve student learning outcomes and increase their interest in learning in elementary schools. An effective combination of appropriate teaching techniques and technological support has been shown to improve student understanding, enthusiasm, and learning outcomes at the elementary school level. Thus, educators must continue to innovate and keep up with technological advances in order to provide optimal learning experiences for their students.